Somatic cell nuclear transfer : history, future and potential application in the bubaline species - Sansiñena, Marina Julia (2011)
Fil: Sansiñena, Marina Julia. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina